Dogwood Anthracnose: A Threat to Flowering Dogwood - Eric Holzmueller; Shibu Jose; Alan Long (EDIS)
FOR-127, a 3-page illustrated fact sheet by Eric Holzmueller, Shibu Jose, and Alan Long, describes this non-native disease threatening flowering dogwood populations in the eastern United States, signs of the disease, what you can do about it, and references. Published by the UF School of Forest Resources and Conservation, October 2007.